2016
DOI: 10.4047/jap.2016.8.6.504
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surface treatment methods on the shear bond strength of auto-polymerized resin to thermoplastic denture base polymer

Abstract: PURPOSEPolyamide polymers do not provide sufficient bond strength to auto-polymerized resins for repairing fractured denture or replacing dislodged denture teeth. Limited treatment methods have been developed to improve the bond strength between auto-polymerized reline resins and polyamide denture base materials. The objective of the present study was to evaluate the effect of surface modification by acetic acid on surface characteristics and bond strength of reline resin to polyamide denture base.MATERIALS AN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…3 Therefore, the bond strength of the TDBR's may be affected if used clinically and surface modification is necessary to enhance the bond strength between the thermoplastic denture base resin and relining resin. Several studies showed that the use of silica coating, 12,18 acetic acid, 9 and tribochemical silica coating combined with 4-methacryloyloxyethy trimellitate anhydride (4-META)/ methyl methacrylate (MMA) -tributylborane (TBB) 3 can improve the strength between denture bases. Although there were many attempts to improve the adhesive properties of denture base resin, limited research has been focused on thermoplastic denture base resin material.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3 Therefore, the bond strength of the TDBR's may be affected if used clinically and surface modification is necessary to enhance the bond strength between the thermoplastic denture base resin and relining resin. Several studies showed that the use of silica coating, 12,18 acetic acid, 9 and tribochemical silica coating combined with 4-methacryloyloxyethy trimellitate anhydride (4-META)/ methyl methacrylate (MMA) -tributylborane (TBB) 3 can improve the strength between denture bases. Although there were many attempts to improve the adhesive properties of denture base resin, limited research has been focused on thermoplastic denture base resin material.…”
Section: Discussionmentioning
confidence: 99%
“…1,9-11 Therefore, it does not provide sufflcient bond strength to autopolymerized resins for repairing fractured dentures or replacing dislodged teeth. 9,10,12 Plasma treatment has been used to modify the surface of products in the industrial world. 13 Nonthermal plasma (NTP) treatment is made of partially ionized gas with ions, electrons, and uncharged particles such as atoms, molecules, and radicals.…”
Section: 대한치과보철학회지 56권 3호 2018년 7월mentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the curing technique and resin materials, different samples from each group were scratched and attenuated for total reflection Fourier transform infrared spectroscopy analysis (ATR-FTIR tensor 27, Bruker, Germany) to detect the component of chemical functional groups formed on the surface of the polyamide nylon base and poly(methyl-methacrylate) (PMMA) repair materials which were processed by different polymerization techniques. The infrared spectra of the experimental samples were recorded in the region 400–4000 cm −1 at a spectral resolution of 4 cm −1 [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…Koodaryan and Hafezeqoran [ 23 ] revealed that the surface treatment of polyamide denture base with 5% acetic acid in aqueous ethanol (30/70 by volume) for 10 minutes may be an efficient and cost-effective method for increasing the shear bond strength to the autopolymerized reline resin.…”
Section: Introductionmentioning
confidence: 99%